KEPADATAN DAN POLA PERTUMBUHAN KERANG LOKAN (Geloina erosa, Solander 1786) DI EKOSISTEM MANGROVE BELAWAN - Hasan, Uswatul; Wahyuningsih, Hesti; Jumilawaty, Erni (Fakultas Perikanan dan Kelautan Universitas Riau, 2014)
Density and growth pattern mangrove clam Geloina erosa (Solander 1786) inmangrove ecosystem Belawan, has been investigated in December 2013 - February2014. G erosa samples taken from three observation stations and each station observa-tions were made 3 replicates (months) sampling. The method used in determining thesampling point is the